Tri-Band Bidirectional Antenna for 2.4/5 GHz WLAN and Ku-Band Applications - Suthasinee Lamultree; Wutthipong Thanamalapong; Sitthichai Dentri; Chuwong Phongcharoenpanich (Applied Sciences, 2022)
A compact tri-band, low profile, and lightweight antenna is proposed for 2.4/5 GHz WLAN and Ku-band applications. The antenna geometry was a radiating rectangular patch surrounded by a wide circular slot with an inverted-L strip connected to one side of the slot. It was mounted on a copper layer of a single side FR4 substrate with a dielectric constant of 4.3 and a height of 1.6 mm. It was fed by a 50-Ω coplanar waveguide. This design was very compact (40 × 40 × 1.6 mm3). Simulated and actual measurements of an antenna setup in the laboratory verified that the antenna’s bidirectional radiation pattern completely covered the three transmission bands: 2.4–2.485 GHz, 5.15–5.825 GHz and 13.4–17.7 GHz with less than 10-dB return loss and maximum gains of 2.35 dBi, 4.41 dBi and 4.71 dBi, respectively. Wireless communication for the self-navigated vehicle, for one example, is fully supported by this single antenna.
Keywords: Antenna Design and Analysis; Millimeter-Wave Propagation and Modeling; Bluetooth and Wireless Communication Technologies